The application of the theory of efficient breach in contract law : a comparative law and economics perspective / Wenqing Liao. - Liao, Wenqing, 1988- (Ius commune europaeum, 2015)
This book analyses the theory of efficient breach in English sales law, European Union contract law and Chinese contract law. It analyses the framework of the efficient breach theory and reconsiders the implications of this theory. According to the traditional efficient breach theory, the remedy of expectation damages is able to motivate efficient breach, which brings the breaching party economic surplus without making the non-breaching party worse off. The essential problems are how to motivate contract parties to make rational decisions and how to solve cases where performance of a contract turns out to be less efficient after its conclusion. The second part of the book further extends the efficient breach theory to the study of contract law systems by analysing how exactly those laws react to breach and what solutions are adopted by them.The comparison of these three systems is more than a mere description of the differences and similarities in the content. More importantly, this comparative research also analyses whether or not the differences between these systems will influence the level of efficiency produced by each legal system by taking account of the different traditions and the concepts of contracts involved in each legal system. Researchers in contract law will also be interested in this approach, particularly for re-thinking the question of whether one legal system is definitely better or worse than the other two.